PENGEMBANGAN VIRTUAL LABORATORY PADA MATERI KINEMATIKA DENGAN ANALISIS VEKTOR DALAM PEMBELAJARAN FISIKA DI KELAS XI SMA - Arna Putri (Universitas Negeri Padang, 2013)
Some of Physics matter’s phenomenon is cannot be observed directly. The abstract phenomenon make experiment activity in laboratory had the hands tied. One alternative to overcome the problem was make the abstract phenomenon can be observed by student in learning activity by using Virtual Laboratory. The general objective of this research was to produce a Virtual Laboratory for physics material “Kinematics with Vector Analysis” Grade XI SMA that has a good validity, practicallity, and effectivity. The type of this research was Research and Development (R & D). To reach objective above, steps done was: 1) identificated potential and problem, 2) collected information, 3) designed product, 4) validate design (with 5 experts), 5) product revision, 6) tested product. Based on the data analysis which has been done, it can present the research results. First, Virtual Laboratory for physics material “Kinematics with Vector Analysis” for grades XI SMA. Second, Virtual Laboratory has a high validity with average value of 81, 67. Third, the value of practicality of Virtual Laboratory was 78, 57 of teacher assessment, 83,22 of student assessment, and 86,54 of observer assessment. Fourth, Virtual Laboratory was effective base on student assessment (81,08). The effectivity of Virtual Laboratry was also signed by the increasing of student’s physics mark. Keywords – Virtual Laboratory, experiment, physics learning